Kinerja Pegawai dalam Proses Perencanaan Pembangunan Partisipatif Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah di Kabupaten Jeneponto - Yansar, Yansar; Madani, Muhlis; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to find out how the performance of employees in the participatory planning process carried out by the Regional Development Research and Development Planning Agency (Bappeda) of Jeneponto Regency. This study used descriptive qualitative research methods. This study used three data collection techniques were observation, interviews with 8 informants and documentation. While data analysis used data reduction, data presentation and drawing conclusions. The results of this study showed that the community participates in the development planning process but in its implementation it was found that development realization was not in accordance with the community’s proposal. The conclusion of this study was that community participation could determine how their proposals were realized in real development.